2022
DOI: 10.1186/s12903-022-02429-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fluoride-containing toothpastes associated with different technologies to remineralize enamel after pH cycling: an in vitro study

Abstract: Background To evaluate the efficacy of fluoride-containing toothpastes with different technologies to remineralize artificial caries lesions in enamel. Methods Bovine enamel blocks were divided into three thirds: intact (untreated), demineralized (artificial caries lesion), and treated (caries lesion, pH cycling with dentifrices). Enamel blocks were randomly distributed into five groups (n = 12): Fluoride-free toothpaste, Colgate Oral Care (NC); Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…These studies would seem to validate the purpose of this review, namely, to determine whether products containing zinc–carbonate hydroxyapatite can be considered a viable alternative to fluorine or other prophylactic systems in terms of remineralization. It is known based on the literature that fluoride is a remineralizing agent [ 27 , 28 , 29 ]. CCP-ACP also appears to be another valuable system [ 30 , 31 , 32 , 70 ] for reducing dental sensitivity [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies would seem to validate the purpose of this review, namely, to determine whether products containing zinc–carbonate hydroxyapatite can be considered a viable alternative to fluorine or other prophylactic systems in terms of remineralization. It is known based on the literature that fluoride is a remineralizing agent [ 27 , 28 , 29 ]. CCP-ACP also appears to be another valuable system [ 30 , 31 , 32 , 70 ] for reducing dental sensitivity [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…With repeated use over time, fluoride can become part of the crystalline structure of the hydroxyapatite, taking the place of the hydroxyl ion and forming fluoroapatite in the post-eruptive phase of the dental element. Toothpastes with a high fluorine content (>1500 ppm) have proved useful in increasing the level of fluoride in saliva throughout the day, changing the acidogenicity of interproximate plaque, increasing the buffering activity of saliva and decreasing the level of Streptococcus mutans [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microhardness of enamel surfaces in the 8 experimental groups (n=5) after pH-cycling (SMH2) were recorded following the same specifications previously mentioned. The surface microhardness recovery ratio (%SMHRR) for each sample was then calculated based on the following formula (Equation 2 ) [ 24 , 29 , 32 , 35 , 37 ]: …”
Section: Methodsmentioning
confidence: 99%
“…The existing research has emphasized the prevention of demineralization and the promotion of remineralization before restoring the tooth [6,7]. There are two main types of remineralization technology used in dentistry techniques, including those that improve fluoride effectiveness and those that mimic the natural healing mechanisms [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the utilization of lasers in contemporary dentistry has seen substantial expansion [11]. Previous experimental studies have shown that CO 2 laser irradiation can cause melting and subsequent recrystallization in dental hard tissues, leading to an enhanced resistance to acidic substances [7,12]. Laser irradiation has been proposed as a method to improve the effectiveness of topical fluoride treatment by increasing fluoride absorption into the enamel and promoting the conversion of hydroxyapatite into fluorapatite crystals [13,14].…”
Section: Introductionmentioning
confidence: 99%